INCREASE THE SERVICE LIFE OF THE INDUCTION FURNACE BASED ON THE DEVELOPMENT OF ITS LINING (Web of Technology: Multidimensional Research Journal, 2025)
In this article, in the process of melting metal in an acid induction furnace, the destruction of the furnace lining depending on the heat and chemical composition of charge materials was taken into account, and the importance of processing liquid metal with slag-forming modifiers was tested in research.